Amusement Park Physics in Panggon Lunjak (Trampoline): Analysis of Kinematics and Energy Use Video Tracking - Akhmad Yusuf; Ishafit Ishafit; Toni Kus Indratno (Universitas Sebelas Maret, 2017)
Panggon Lunjak (trampoline) is one of the famous amusement parks among the people that we can use as a recreation to enjoy a pleasant sensation. Without us knowing the amusement park that we often encounter is actually the result of the application of science and technology, especially in the field of physics, because it is amusement park for student of science is a real laboratory or the giant laboratory that we can use as a study of physics concepts and as research materials. Panggon Lunjak (trampoline) motion is very close to the harmonic motion where the resulting graph of the sinus so that on the graph will be in the analysis of kinematics and energy phenomena, so that research on simple harmonic motion materials is not limited to research using pendulum motion and spring load motion which is often exemplified as research on harmonic motion. The purpose of this study is to analyze the physical aspects of Panggon Lunjak (trampoline) motion based on the laws of physics on the concept of kinematics and analyze energy, Where the mechanical energy of addition between potential energy and kinetic energy (Conservation of energy). The analysis is done by using video tracking. Based on the analysis done using people as a mass, the result of the amplitude, the spring constant, angular frequency, and the law of conservation of energy on the Panggon Lunjak (trampoline) is true. This analysis activity will be well used as a physics learning for students.